Habitat translocation, rebuilding biodiversity and no net loss of biodiversity. (23rd December 2013) - Box, John
Abstract Recent reviews of the priority policy options and research needs for nature conservation have identified the importance of new land use policies for restoring and rebuilding biodiversity including habitat banking, 'no net loss' of biodiversity, restoring flood plain functionality and ecologically coherent networks. Such policies are usually delivered by habitat creation, habitat restoration and habitat enhancement. Habitat translocation is another mechanism that can contribute to the delivery of these policies. Habitats can be restored and created by translocating ecological resources from sites as part of ongoing habitat management, where habitat diversity or early successional habitats are required. Habitat translocation can be used to salvage ecological features and their associated ecosystem services from sites for consented or permitted development projects. Critical success factors for translocation of aquatic and terrestrial habitats are identified. New policy issues and research topics relating to habitat translocation are proposed.